Design and implementation of low cost automation system in heavy vehicle brakes assembly line. (16th February 2009) - Samuel, G.L.; Darwin, M.
The brake drum assembly is an essential component in the automobiles. With increasing demand for heavy-duty automobiles, like trucks and buses, there is an increasing demand for these components. With a typical assembly rate of about 400 units a day using manual assembly tools, there is enormous pressure on the operator, prohibiting the company from enhancing their production rates to meet the market demand with existing resources. Keeping in mind the volatility of the market, it is preferred to resort to low cost automation, a technology that creates some degree of automation around the existing resources, using mostly standard components available in the market with very low investment. The method reported here presents such a low cost automation solution. It has been implemented in the real production line and its effectiveness has been proved in terms of planned objectives of increased productivity and reduced operator fatigue.